CBMT-26. SERIAL CHARACTERIZATION OF HYPERPOLARIZED [1-13C]PYRUVATE METABOLISM IN PATIENTS WITH GLIOMA AND THE INFLUENCE OF BEVACIZUMAB. (11th November 2019) - Autry, Adam; Gordon, Jeremy; Chen, Hsin-Yu; Lafontaine, Marisa; Villanueva-Meyer, Javier; Chang, Susan; Xu, Duan; Larson, Peder; Vigneron, Daniel; Li, Yan
Abstract: Treatment-related changes often mimic or mask tumor on standard anatomic imaging, making it difficult to monitor disease recurrence. Hyperpolarized (HP) carbon-13 MR imaging allows for real-time non-invasive measurement of metabolism, which may improve patient surveillance. Here, we focused on characterizing serial HP scans in patients undergoing treatment compared to healthy controls. Serial dynamic HP C-13 MRI scans were performed on 5 patients with recurrent glioma (22 total) and 3 healthy controls (4 total) using an echo-planar imaging sequence (2.88-8cm 3 spatial resolution, 3s temporal resolution, 60s), following injection of 0.43mL/kg of 250mM HP [1- 13 C]pyruvate. Apparent rate constants were modeled for enzymatic conversion of pyruvate-to-lactate (kPL ) via cytosolic lactate dehydrogenase and pyruvate-to-bicarbonate (kPB ) via mitochondrial pyruvate dehydrogenase and carbonic anhydrase. Regions of interest included normal-appearing white matter (NAWM) and T2-hyperintense lesions (T2L), which were segmented from H-1 MR images and then aligned to the HP data. Carbon voxels containing >30% of NAWM or T2L were included in the analysis. Healthy controls demonstrated consistent kPL and kPB values over 4 scans in NAWM with SD/Mean of 5% and 12%, respectively. Compared to the median kPL-NAWM of 0.022s -1 in controls, the 5 patients had median serial kPL-NAWM values of 0.023, 0.023, 0.023, 0.029, and 0.015s -1, and mean serial ratios of kPL between T2L and NAWM (kPL-T2L /kPL-NAWM ) of 1.22, 1.27, 1.05, 1.32, and 1.37s -1, indicating higher values in putative tumor. Median kPB-NAWM in controls was 0.004s -1 and ranged in patients 0.003-0.006s -1 . Two patients with >4 serial scans, showed consistent kPL-NAWM over standard-of-care treatment and elevated kPL-T2L within new lesions, but up to 85% increase in kPL-NAWM with bevacizumab, which may be attributed to reduced BBB permeability. Stable patients generally demonstrated consistent kPL-T2L values that were lower compared to progressive patients. Future studies will include multi-parametric 1H imaging analysis in a larger patient population.